Photoshop elements 4.0 maximum performance : - Galer, Mark (Elsevier/Focal, 2006)
A series of creative projects, packed with tips and tricks and illustrated with large, full-color screengrabs, guide you through a wide range of advanced techniques for professional quality editing.